The impact of immersive design on the relations between students’ motivational and science literacy awareness: a mixed methods study - Sun, Yuan-Ke; Chan, Man-Ho; Wong, Wing-Chi (Cogent education, 2025)
This study examines the use of immersive techniques, intrinsic motivation, and instructional approaches to advance science literacy (SL) awareness in STEM education. SL awareness in higher education is defined as the capability to understand, apply, and evaluate fundamental scientific concepts and practices for informed decision-making. We investigated the impact of an immersive design framework on the relationship between intrinsic motivation and SL awareness among sixty-nine Hong Kong STEM students. Following two instructional sessions, participants completed a self-reported questionnaire, which was quantitatively and thematically analysed. Quantitative results revealed that interest significantly improves SL awareness, while relatedness does not. Thematic analysis identified two main themes—motivational layer and cognitive awareness—and further outlined six sub-themes: interest, positive emotion, relatedness, mental representation, cognitive resources, and metacognition, clarifying their roles in enhancing learning. This study confirms that an immersive design framework effectively enhances SL by efficiently utilizing cognitive resources and fostering deep engagement with complex concepts. Future research should investigate extending this design approach to other abstract scientific topics to broaden its educational impact.